EFL Children’s Perception on Reading - Oktarina, Putu Santi; Wilantari, Ni Kadek Tia Wiat (Institut Hindu Dharma Negeri Denpasar, 2021)
Reading has a very significant effect towards individuals’ life. English in Indonesia as a foreign language, so there are many possibilities which the English language students get difficulties in understading reading text. EFL young learners are also still struggling to overcome their reading problems. This research was conducted to find out the EFL children’s reading problem. The data were collected through questionnare and explained descriptively. The questionnare consists of ten questions which is made based on the rubric of reading. The respondents of this research were the 20 students from the fourth grade. The results of the research that the EFL children’s reading problem are students seldom pay attention to punctuation in reading English, students always have difficulty to distinguish the pronunciation of words in English, students always need a long time to understand the reading text in English, students never look for the main idea of the reading text which they read, students have poor reading habit because they unusual read in English or seldom read in English, students seldom even never understand the grammar structures in English when reading, students never even seldom pay attention to the form or the content of the reading text which they read, students never apply any strategies in reading English, students lack of vocabulary when reading English so that they need a dictionary to comprehend the reading text in English, and students do not like or not interested reading English because they are seldom reading in English. Thus, the questionnare show the EFL children’ reading problem.